1986
DOI: 10.1002/cne.902460405
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde transport of fluorescent tracers reveals extensive ipsi‐ and contralateral claustrocortical connections in the rat

Abstract: The projections from the claustrum to the cerebral cortex in the rat were examined by means of retrogradely transported fluorescent tracers Fast Blue (FB) and Diamidino Yellow dihydrochloride (DY), injected in the prefrontal, motor, somatosensory, auditory, and visual fields. In all cases, substantial numbers of retrogradely labeled neurons were observed in the ipsilateral and moderate to scant numbers in the contralateral claustrum insulare. Symmetrical bilateral injections of FB and DY as well as simultaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 54 publications
9
59
0
Order By: Relevance
“…These findings are generally consistent with recent studies (Minciacchi et al, 1985;Sloniewski et al, 1986b).…”
Section: Efferent Connections Of the Anterior Claustrumsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings are generally consistent with recent studies (Minciacchi et al, 1985;Sloniewski et al, 1986b).…”
Section: Efferent Connections Of the Anterior Claustrumsupporting
confidence: 83%
“…First, it has long been shown that the claustrum is a cortically related structure originating from the cortex (Meynert, 1868;Brodmann, 1909;de Vries, 1910;Macchi, 1951;Filiminoff, 1966;Bayer and Altman, 1991;Bayer et al, 1993), whereas the dorsal endopiriform nucleus is generated in the palliostriatal ventricular angle (Bayer and Altman, 1991;Bayer et al, 1993). Second, the claustrum is heavily and reciprocally connected with neocortex (Druga, 1972(Druga, , 1982Carey and Neal, 1985;Minciacchi et al, 1985;Morys and Sloniewski, 1986;Sloniewski et al, 1986b;Druga et al, 1990;Clasca et al, 1992;Dinopoulos et al, 1992;Kowianski et al, 1996Kowianski et al, , 1998aSadowski et al, 1997a,b), whereas the dorsal endopiriform nucleus is mainly connected with the piriform, entorhinal, insular, and orbital cortices Price, 1977a,b, 1878a,b;Haberly and Price, 1978;Markowitsch et al, 1984;Wilhite et al, 1986;Witter et al, 1988;Behan and Haberly, 1999).…”
Section: Results Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…This binding may be effected inside the claustrum in the manner we have suggested. Also, even if the input to claustral cells is unimodal, the output axons from claustral P cells commonly bifurcate and project to more than one modal type of cortex (Divac et al, 1978;Divac, 1979;Sloniewski et al, 1986;Rahman and Baizer, 2007). The experiments reported by Remedios et al (2010) only produce strong evidence that the input to individual claustral P cells in not intermodal.…”
Section: The Saliency Detection Hypothesismentioning
confidence: 99%
“…It has been claimed that areas of the claustrum in the cat sends "precisely reciprocal" projections back to those area(s) of the cortex whence its inputs derived Sherk and LeVay, 1981;Sherk, 1986). It has also been claimed that the projections to and from the claustrum are diffuse, but quite specific, in both directions (one point to specific points) (Divac et al, 1978;Divac, 1979;Sloniewski et al, 1986). Single cells in the claustrum have been reported to send branched axons to several cortical areas.…”
Section: Introductionmentioning
confidence: 99%